»In der Art von Inschriften«. Emblematische Inschriftendichtung als Darstellungsprinzip von Ferdinand von Fürstenbergs Monumenta Paderbornensia (1669 und 1672) - Süßmann, Johannes (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornensia des Ferdinand von Fürstenberg)

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

Optimized, Highly Efficient Silicon Antennas for Optical Phased Arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
Silicon photonics, in conjunction with complementary metal-oxide-semiconductor (CMOS) fabrication, has greatly enhanced the development of integrated optical phased arrays. This facilitates a dynamic control of light in a compact form factor that enables the synthesis of arbitrary complex wavefronts in the infrared spectrum. We numerically demonstrate a large-scale two-dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing elegant radiation patterns in the far-field. For a wavelength of 1.55 μm, we optimize two antennas for the OPA exhibiting an upward radiation efficiency as high as 90%, with almost 6.8% of optical power concentrated in the field of view. Additionally, we believe that the proposed OPAs can be easily fabricated and would have the ability to generate complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation, and augmented-reality displays.
Keywords: tet_topic_opticalantenna

How to suppress radiative losses in high-contrast integrated Bragg gratings - Hammer, Manfred; Farheen, Henna; Förstner, Jens (Journal of the Optical Society of America B)
High-contrast slab waveguide Bragg gratings with 1D periodicity are investigated. For specific oblique excitation by semi-guided waves at sufficiently high angles of incidence, the idealized structures do not exhibit any radiative losses, such that reflectance and transmittance for the single port mode add strictly up to one. We consider a series of symmetric, fully and partly etched finite gratings, for parameters found in integrated silicon photonics. These can act as spectral filters with a reasonably flattop response. Apodization can lead to more box shaped reflectance and transmittance spectra. Together with a narrowband Fabry–Perot filter, these configurations are characterized by reflection bands, or transmittance peaks, with widths that span three orders of magnitude.
Keywords: tet_topic_waveguide

Rezension zu T. Fohr: Integrierte Sprachbildung im Fach Kunst. Eine Studie zur Sekundarstufe I, Klasse 5. - Stenzel, Nadja (Rezension zu T. Fohr: Integrierte Sprachbildung im Fach Kunst. Eine Studie zur Sekundarstufe I, Klasse 5.)

Optimized silicon antennas for optical phased arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate a large-scale two dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing desired radiation patterns in the far-field. The OPAs are numerically optimized to have an upward efficiency of up to 90%, targeting radiation concentration mainly in the field of view. We envision that our OPAs have the ability of generating complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation and augmented-reality displays.
Keywords: tet_topic_opticalantenna

Increasing the upward radiation efficiency of optical phased arrays using asymmetric silicon horn antennas - Farheen, Henna; Joshi, S.; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (2023 IEEE Photonics Conference (IPC))
A key challenge in designing efficient optical phased arrays is the lack of a well-designed radiator. This work explores horn antennas numerically optimized to target high upward radiation efficiency to be employed in silicon-based phased arrays capable of producing elegant radiation patterns in the far-field.
Keywords: tet_topic_opticalantenna

Journal Netzwerk Frauen- und Geschlechterforschung - Bünning, Jenny; Kortendiek, Beate; Radermacher, Clara; Schmidt, Uta C. (Journal Netzwerk Frauen- und Geschlechterforschung NRW)

¿Qué es la instapoesía? Literarästhetisches Lernen mit Gedichten auf Instagram - van der Valk, Stefanie (Der fremdsprachliche Unterricht Spanisch)

Interreligious Open Theology and Human Exceptionalism: In Conversation with Catherine Keller - Grössl, Johannes (Open and Relational Theology and Its Social and Political Implications. Muslim and Christian Perspectives)

T&T Clark Handbook of Suffering and the Problem of Evil

Paderborner Qualitätsstern (PQ³): A self-evaluation instrument for ECEC and school educators to reflect collaboration in transition processes. Current findings. Presentation for self-organised symposium on the EECERA Conference "Children´s Curiosity, Agency and Participation: challenges for professional Action and Development" in Lisbon (Portugal) - Büker, Petra; Höke, Julia; Herding, Jana
September 2023

„FInDig“: Fach – Inklusion – Digitalisierung vernetzen. Ein Planungs- und Reflexionsmodell für die Lehrkräftebildung - Häsel-Weide, Uta; Schmidt, R.; Büker, Petra (Zeitschrift für Schul- und Professionsentwicklung (PFLB))

FInDig: Fach – Inklusion – Digitalisierung vernetzen. Ein Planungs- und Reflexionsmodell für die Lehrkräftebildung - Büker, Petra; Häsel-Weide, Uta; Schmidt, Rebekka (Tagung „Digitalisierungsbezogene Lehrer*innenbildung an der Universität Paderborn)

Schöpfungsrisiko oder Erlösungsgarantie? Theologische Herausforderungen analytischer Vorsehungskonzeptionen - Grössl, Johannes (Vorsehung und Handeln Gottes. Analytische und kontinentale Perspektiven im Dialog (QD 331))

Can God Know the Future – and Share his Knowledge with Human Beings? An Open and Relational Account of Prophecy - Grössl, Johannes (God’s Own Mouthpieces: Reason and Prophecy in Judaism, Christianity and Islam)

Galois groups of (ⁿ₀)+(ⁿ₁)X+…+(ⁿ₆)X⁶ - Klahn, B.; Technau, Marc (Int. J. Number Theory)

Bias in the number of steps in the Euclidean algorithm and a conjecture of Ito on Dedekind sums - Minelli, P.; Sourmelidis, A.; Technau, Marc (Math. Ann.)

Forms of Understanding of XAI-Explanations - Buschmeier, Hendrik; Buhl, Heike M.; Kern, Friederike; Grimminger, Angela; Beierling, Helen; Fisher, Josephine; Groß, André; Horwath, Ilona; Klowait, Nils; Lazarov, Stefan; Lenke, Michael; Lohmer, Vivien; et al. (arXiv:2311.08760)
Explainability has become an important topic in computer science and artificial intelligence, leading to a subfield called Explainable Artificial Intelligence (XAI). The goal of providing or seeking explanations is to achieve (better) 'understanding' on the part of the explainee. However, what it means to 'understand' is still not clearly defined, and the concept itself is rarely the subject of scientific investigation. This conceptual article aims to present a model of forms of understanding in the context of XAI and beyond. From an interdisciplinary perspective bringing together computer science, linguistics, sociology, and psychology, a definition of understanding and its forms, assessment, and dynamics during the process of giving everyday explanations are explored. Two types of understanding are considered as possible outcomes of explanations, namely enabledness, 'knowing how' to do or decide something, and comprehension, 'knowing that' -- both in different degrees (from shallow to deep). Explanations regularly start with shallow understanding in a specific domain and can lead to deep comprehension and enabledness of the explanandum, which we see as a prerequisite for human users to gain agency. In this process, the increase of comprehension and enabledness are highly interdependent. Against the background of this systematization, special challenges of understanding in XAI are discussed.

Modeling Highlighting of Metaphors in Multitask Contrastive Learning Paradigms - Sengupta, Meghdut; Alshomary, Milad; Scharlau, Ingrid; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: EMNLP 2023)
Metaphorical language, such as {“}spending time together{”}, projects meaning from a source domain (here, $money$) to a target domain ($time$). Thereby, it highlights certain aspects of the target domain, such as the $effort$ behind the time investment. Highlighting aspects with metaphors (while hiding others) bridges the two domains and is the core of metaphorical meaning construction. For metaphor interpretation, linguistic theories stress that identifying the highlighted aspects is important for a better understanding of metaphors. However, metaphor research in NLP has not yet dealt with the phenomenon of highlighting. In this paper, we introduce the task of identifying the main aspect highlighted in a metaphorical sentence. Given the inherent interaction of source domains and highlighted aspects, we propose two multitask approaches - a joint learning approach and a continual learning approach - based on a finetuned contrastive learning model to jointly predict highlighted aspects and source domains. We further investigate whether (predicted) information about a source domain leads to better performance in predicting the highlighted aspects, and vice versa. Our experiments on an existing corpus suggest that, with the corresponding information, the performance to predict the other improves in terms of model accuracy in predicting highlighted aspects and source domains notably compared to the single-task baselines.